(untitled) (Proceedings of the International Conference on Education, 2019)
The research deals with the notion of psychological training of students’ professional direction, with the analysis of training peculiarities. The alternative of communicative English teaching at higher educational institutions to the training of professional direction is substantiated. The level of professionalism has descended for the last decades in Russia. And the basis of professionalism is a high level of professional direction. We consider professional direction as a structural part of personality direction and the system of components, which directs personality behavior and activity to obtaining professional skills, their development and mastering. The most famous and effective way of development of personality’s professional direction is a psychological training. The principles of the training are voluntary participation, “here and now”, partner communication, proactive attitude, feedback, confidentiality, and principles of humanistic psychology, i.e. unbiased attitude, acceptance of other people, psychological safety and support. But the psychological training is not available in the educational process of the university. The research in which all the mentioned pedagogical and psychological conditions had been created was conducted at Yugra State University in the framework of communicative English language teaching. During the research the set of theoretical and empirical methods were used. Among them are system analysis and synthesis, modeling, questionnaire surveys, testing, lesson observation, pedagogical experiment, methods of mathematical statistics. The data obtained as a result of our research proved the effectiveness of communicative language teaching for developing students’ professional direction that points out the possibility of its use instead of the psychological training.